Representations of trauma - Vrečko, Asta (Annales. Series historia et sociologia, 2016)
The graphic novel Italian Winter (L'inverno d'Italia) by Davide Toffolo relays the story of two children, Drago and Giudita, who are interned in the Italian Fascist concentration camp Gonars. The paper will analyse the work and examine its visual language regarding to the content. For the interpretation of the work as a representation of trauma a comparison between Italian Winter and the acclaimed graphic novel Maus by Art Spiegelman. Since Maus has inspired new concepts in the interdisciplinary field of memories studies, this paper builds on some of them for an interpretation of Italian Winter.
Keywords: concentration camp art; Gonars; graphic novel; Italian Winter; Italijanska zima; L'inverno d'Italia; Maus; postmemory; postspomin; roman v stripu; Spiegelman, Art, 1948-; taboriščna umetnost; Toffolo, Davide, 1965-; traumatic realism; travmatični realizem